12 Transformative Relocation in the U.S. Southwest and Mesoamerica. Issue 1 (March 2014) - Nelson, Ben A.; Chase, Adrian S. Z.; Hegmon, Michelle; Chase, Arlen F.; Scarborough, Vernon L.
ABSTRACT A comparative perspective, drawing from cases in the U.S. Southwest and Northern Mexico, is used to illuminate the iconic Classic Maya "collapse, " and to define the concept of transformative relocation. In some of the cases we discuss—including La Quemada and Classic Mimbres, as well as Maya—the end of a social configuration is not the end of a people. Rather, a broad temporal and regional perspective demonstrates that the dramatic change we see in the archaeological record is best characterized as a transformative relocation in which people relocated themselves and adopted new ways of life. The comparative perspective allows us to identify factors that contribute to this kind of transformation, including a compounding of vulnerabilities and situations of path dependence.